Population dynamics of the invasive crayfish (Procambarus clarkii Girard, 1852) at two marshes with differing hydroperiods - Anastácio, Pedro M. (2012)
The population dynamics of the red swamp crayfish (Procambarus clarkii Girard, 1852) was studied from May 2005 to May 2006 in a pond (PCD) subjected to drought between June and December and in a continuously flooded rice field drainage channel (PMG) located in the Tejo river basin, Portugal. The proportion of females in the population was not independent from the season and was negatively correlated with both female and male maturation status. Male and female maturation was synchronous but males remained in a reproductive form after recruitment while females reverted quickly to lower maturation indexes. At PCD and PMG, respectively 2 and 5 cohorts were detected by modal analysis. Large crayfish were abundant in spring, summer and early autumn and juveniles were abundant in autumn, especially at PCD. Crayfish density at PCD was lower than at PMG and mortality rate (Z) was 3.99 at PCD and 2.43 at PMG. The average lifespan of the crayfish populations was 91 days at PCD and 150 days at PMG. Our study indicated faster growth and larger maximum sizes at the site with the more stressed environment and lowest relative crayfish densities (PCD), suggesting that any exploitation or control strategies for these two populations should consider management of the hydroperiod and of maximum crayfish densities.